Desenvolvimento de eletrodos de carbono vítreo modificados com nanotubos de carbono funcionalizados imobilizados em filmes de hidrocloreto de poli(alilamina) para determinação de fármacos - Takeda, Humberto Hissashi (2011)
Research involving carbon nanotubes (CNT) have a great attraction since its synthesis to the technology application. As part of the work was studied the formation and the stability of a functionalized Multiwall Carbon Nanotubes (MWCNTs) dispersion in a hydrochloride poly(allylamine) (PAH) polyelectrolyte solution 1.2 x 10-4 mol L-1 (MWCNTs/PAH) in order to use it for surface modification of a glassy carbon electrodes (GCE) by casting technique. Zeta potential measurements confirmed the stability of the MWCNTs/PAH dispersion. After this study were carried out modifications of GCE surfaces with the MWCNTs/PAH (GCE-MWCNTs/PAH) dispersion and found the electrochemical behavior of the film formed by cyclic voltammetry with potassium hexacyano ferrate (III) 6,6 x 10-4 mol L-1 in a potassium chloride solution 0, 1 mol L-1. The results proved the electrochemical effect provided by the MWCNTs and with the Randles-Sevcik equation we have obtained an active area for GCE-MWCNTs/PAH 1.2 times higher compared to the GCE bare. For further study, we evaluated the GCE-MWCNTs/PAH performance in a pharmaceuticals formulations with voltammetric and amperometric determinations, ciprofibrate, dopamine (DA), levodope (L-dopa) and carbidope. The ciprofibrate determination were measured by differential pulse voltammetry (DPV) and was used as supporting electrolyte a solution of sodium phosphate buffer 0.1 mol L-1 (pH 7,0). The analytical curve was linear in the ciprofibrate concentration range from 1.33 x 10-5 to 1.32 x 10-4 mol L-1 with a detection limit of 8.34 x 10-6 mol L-1. For DA determination was measured by amperometric measurement in a potential of 0.2 V in a phosphate buffer solution 0.1 mol L-1 (pH 7.0) as supporting electrolyte, and the analytical curve showed a linearity over the concentration range between 3.32 x 10-6 to 3.32 x 10-5 mol L-1 with a detection limit of 5.7 x 10-7 mol L-1. The L-dopa determination was done with the DPV and was used as a supporting electrolyte a sodium chloride solution (NaCl) 0.1 mol L-1. The analytical curve obtained showed a linearity over the concentration range of 2.00 x 10-6 to 2.72 x 10-5 mol L-1 and the limit of detection was 8.4 x 10-7 mol L-1. The carbidopa determination were measured by DPV and was used as a supporting electrolyte a NaCl solution 0.1 mol L-1 and the analytical curve xv showed a linearity over the concentration range of 2.00 x 10-6 to 2.34 x 10-5 mol L-1 and detection limit obtained was 6.50 x 10-7 mol L-1.